Bacteriological studies on the uterine biopsy and conception rate foil owing treatment in repeat breeding crossbred cows - SHUKLA, S P; SHARMA, R D (The Indian Journal of Animal Reproduction, 2005)
Present study was conducted on 10 normal and 45 repeat breeding crossbred cows. The uteri of normal cows harboured isolates of E. coli, Staphylococci and Streptococci in 30 percent of the cows. The uteri of 91.12% repeat breeder cows yielded either single or mixed bacterial growth. The organisms isolated were E. coli (18.75%), Corynebacterium (15.64%), Bacilli (14.06%), Staphylococci (12.50%), Pseudomonas (12.50%), and Micrococcus species (3.12%). In vitro drug sensitivity of different isolates of bacteria varied greatly between the isolates of different genera. Out of a total of 64 isolates recovered from the uterine biopsies 84.37, 60.93, 67.18, 42.18, 6.25, 20.31, 29.68, 20.31, 38.12, 20.31 and 9.37 percent were found to be sensitive for gentamycin, chloramphenicol, neomycin, oxytetracycline, ampicillin, chlortetracycline, nalidixic acid, erythromycin, streptomycin, cotrirnoxazole and furazolidine, respectively. No isolate was found to be sensitive to penicillin. An overall conception rate of 52.96% was achieved in repeat breeders following treatment. Highest conception rate was recorded in animals treated with gentarnycin (72.72%) followed by oxytracycline (62.50%), chlorarnphenicol (40.00%), streptomycin (40.00%) and nalidixic acid (20.00%).